Part 3. Clinical Practice Guideline for Airway Management and Emergency Thoracotomy for Trauma Patients from the Korean Society of Traumatology - Chan Yong Park; O Hyun Kim; Sung Wook Chang; Kang Kook Choi; Kyung Hak Lee; Seong Yup Kim; Maru Kim; Gil Jae Lee; Korean Society of Traumatology (KST) Clinical Research Group (Journal of Trauma and Injury)
The following key questions and recommendations are presented herein: when is airway intubation initiated in severe trauma? Airway intubation must be initiated in severe trauma patients with a GCS of 8 or lower (1B). Should rapid sequence intubation (RSI) be performed in trauma patients? RSI should be performed in trauma patients to secure the airway unless it is determined that securing the airway will be problematic (1B). What should be used as an induction drug for airway intubation? Ketamine or etomidate can be used as a sedative induction drug when RSI is being performed in a trauma patient (2B). If cervical spine damage is suspected, how is cervical protection achieved during airway intubation? When intubating a patient with a cervical spine injury, the extraction collar can be temporarily removed while the neck is fixed and protected manually (1C). What alternative method should be used if securing the airway fails more than three times? If three or more attempts to intubate the airway fail, other methods should be considered to secure the airway (1B). Should trauma patients maintain normal ventilation after intubation? It is recommended that trauma patients who have undergone airway intubation maintain normal ventilation rather than hyperventilation or hypoventilation (1C). When should resuscitative thoracotomy be considered for trauma patients? Resuscitative thoracotomy is recommended for trauma patients with penetrating injuries undergoing cardiac arrest or shock in the emergency room (1B).